Strengthening OT Networks in Critical Infra structure: A Comprehensive Cybersecurity Strategy Leveraging Trojan Hunt India’s Data Diode and Threat Monitoring (InSKIA and OT SOC) - Sharma, Kunal (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
Operational Technology (OT) networks form the backbone of critical infrastructure, yet they face escalating cybersecurity threats due to growing convergence with IT systems, reliance on legacy technologies, and inadequate protective measures. This capstone explores these vulnerabilities, evaluates recent cyber incidents, and proposes a com prehensive, practical cybersecurity framework integrating Trojan Hunt A India’s Data Diode technology, InSkia Dark Web Monitoring & OT SOC Threat Monitoring. The project highlights weaknesses in traditional f irewalls—particularly their susceptibility to recent remote code ex ecution (RCE) exploits—and underscores the value of physical-layer security and proactive threat monitoring.